2020
DOI: 10.1038/s41467-020-19775-w
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotically-relevant low polyion multivalency can improve functionality of membraneless compartments

Abstract: Multivalent polyions can undergo complex coacervation, producing membraneless compartments that accumulate ribozymes and enhance catalysis, and offering a mechanism for functional prebiotic compartmentalization in the origins of life. Here, we evaluate the impact of lower, more prebiotically-relevant, polyion multivalency on the functional performance of coacervates as compartments. Positively and negatively charged homopeptides with 1–100 residues and adenosine mono-, di-, and triphosphate nucleotides are use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
136
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(160 citation statements)
references
References 55 publications
7
136
0
Order By: Relevance
“…The PArg we used is shorter than PLys, because longer PArg peptides have been found to form aggregates with ATP. 13 We found that (ATP, GTP, or TPP)/PArg could form coacervates and that these coacervates exhibited a temperature dependence: the c s * decreased with increasing temperature in a similar way as for PLys. After linearizing the plot according to eq 4 and fitting the data, we found that intercepts increased in the order G < A, in agreement with our results for PLys-based coacervates (G < A).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…The PArg we used is shorter than PLys, because longer PArg peptides have been found to form aggregates with ATP. 13 We found that (ATP, GTP, or TPP)/PArg could form coacervates and that these coacervates exhibited a temperature dependence: the c s * decreased with increasing temperature in a similar way as for PLys. After linearizing the plot according to eq 4 and fitting the data, we found that intercepts increased in the order G < A, in agreement with our results for PLys-based coacervates (G < A).…”
Section: Resultsmentioning
confidence: 56%
“…All oligonucleotides could be concentrated in (ATP+GTP)/PLys and (AGCT)/PLys coacervate droplets ( K p > 58), as shown in Figure 7 and in agreement with previous findings. 13 , 14 , 62 For (ATP+GTP)/PLys coacervates ( Figure 7 a), poly-C 15 and poly-T 15 exhibit significantly higher partitioning coefficients at 0.10 M salt than poly-A 15 and poly-G 11 , despite the fact that A and G are the more hydrophobic bases, which display stronger base stacking interactions. This difference could be explained by a favorable base pairing interaction between the poly-C 15 and GTP in the coacervates, as well as poly-T 15 and ATP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doublestranded oligonucleotides have been reported to partition less effectively in coacervates of the intrinsically disordered protein, Ddx4, which was interpreted as a consequence of their greater persistence length as compared to single-stranded oligonucleotides. 7,13 Persistence length could be a factor here as well. The outer R10/K10/D10 coacervate phase may have a more open, dynamic mesh-like structure at the nanoscale as compared with the inner phase, consistent with its reduced peptide density and local viscosity.…”
Section: Resultsmentioning
confidence: 98%
“…Both cationic peptides are expected to interact with RNAs via ion pairing with the backbone and cation-pi interactions with the nucleobases, with R10 expected to interact more strongly due to its more favorable cation-pi and pi-pi binding with the nucleobases. 32,33 In comparison to longer peptides (e.g., 100mers), shorter peptides such as these have shown stronger partitioning of oligoRNA 7 and could be more readily engineered to control properties of coacervate droplets for future application. Peptides were combined pairwise (R10/D10 and K10/D10) and all together (R10/K10/D10) to form coacervate droplets (Fig.…”
Section: Resultsmentioning
confidence: 99%